Ambivalensi Dakwah dan Ambisi Politik (Membaca Sisi Tak Terbaca pada Gerakan Dakwah Mahasiswa Pembebasan) - Lufaefi Lufaefi (Laboratorium Prodi Pendidikan Agama Islam UNJ, 2018)
Da'wah is a very sacred teaching in Islam. Its existence is the determination of whether or not the prophetic leaflet. But da'wah in the past is often ignored, as some groups make da'wah a vehicle to satisfy its political ambitions. Da'wah is not infrequently manifested by the politicization of religion in order to vent worldly appetites. So various ways to carry the wheel of da'wah, even in ways of violence. Some groups who have ambition to preach are the GEMA Pembebasan. The da'wah for this group is to replace the democratic system with the system of khilafah islamiyah. So ambiguities and ambivalencies between da'wah and political ambitions are indistinguishable. GEMA Pembebasan claims da'wah movement but its locomotive is politics.